2021
DOI: 10.3138/cjhs.2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Group sex in the time of COVID: Intimacy, learning and community-building in sexual communities during a pandemic

Abstract: Introduction: COVID-19 has had a profound effect on every aspect of contemporary life, including sexuality. Physical distancing measures and limitations on large gatherings explicitly restrict in-person group sex events. We sought to understand how the pandemic and associated public health control measures have affected group sex practitioners and activities. Methods: We used a community-based participatory research approach. In fall 2019, we recruited a Community Advisory Board (CAB) of group sex key informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic has impacted nearly every aspect of people's lives in some fashion [1]. During and even after country lock-down phases, individuals changed their sexual activities to follow public health guidance [2]. Along with the COVID changes, the General Social Survey [3], showed a decrease in adults saying they did not have sex once within the past year-from 23% in both 2016 and 2018 to 26% in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has impacted nearly every aspect of people's lives in some fashion [1]. During and even after country lock-down phases, individuals changed their sexual activities to follow public health guidance [2]. Along with the COVID changes, the General Social Survey [3], showed a decrease in adults saying they did not have sex once within the past year-from 23% in both 2016 and 2018 to 26% in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, a recent qualitative investigation of CNM parents found that parents spent less time with non-cohabiting partners during the May-December 2020 period of the pandemic (Manley & Goldberg, 2021 ). However, CNM parents also deployed creative responses by queering family practices, which include some combination of disengagement with non-cohabiting partners, connecting over technology, having partners move in with them, and incorporating their non-cohabiting partner into their quarantine pod or bubble (Manley & Goldberg, 2021 ; Fournier et al, 2021 ). The degree to which these challenges or opportunities are reflected in discourse surrounding Covid-19 may highlight the role of social media in identity-making communication for these two communities, which we elaborate on in the next section.…”
Section: Introductionmentioning
confidence: 99%